2021
DOI: 10.1186/s13722-021-00248-4
|View full text |Cite
|
Sign up to set email alerts
|

A Health Technician-delivered Brief Intervention linked to AUDIT for reduction of alcohol use in Chilean primary care: a randomized controlled trial

Abstract: Background Because of the shortage of health professionals in Chilean primary care, Health Technicians (HT) are providing Brief Interventions (BI) for risky alcohol consumption. We compared the efficacy of two AUDIT-linked interventions provided by HTs: an informative leaflet and a BI plus leaflet. Methods This is a parallel-group randomized controlled trial with 1:1 randomization. Participants were identified through screening with the Alcohol Use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The average age of participants was 35.68 years (average age ranged from 18.99 to 62.83 years), and 67% ( n = 4790) of participants were male. Of the 19 RCTs included in this systematic review, 17 studies used AUDIT as an outcome (and were included in the primary analysis) [37–41, 43–52, 54, 55], while two used the AUDIT‐C (and were added to the secondary analysis) [42, 53]. Three studies (Hansson et al ., Safsten et al ., Xiaolu et al .)…”
Section: Resultsmentioning
confidence: 99%
“…The average age of participants was 35.68 years (average age ranged from 18.99 to 62.83 years), and 67% ( n = 4790) of participants were male. Of the 19 RCTs included in this systematic review, 17 studies used AUDIT as an outcome (and were included in the primary analysis) [37–41, 43–52, 54, 55], while two used the AUDIT‐C (and were added to the secondary analysis) [42, 53]. Three studies (Hansson et al ., Safsten et al ., Xiaolu et al .)…”
Section: Resultsmentioning
confidence: 99%
“…Then, mixed-effects regressions were used to adjust for demographic variables as fixed-effects (age, sex, and educational level) and the health center as random effects. See the main paper for a detailed description of the trial [ 4 ].…”
Section: Methodsmentioning
confidence: 99%
“…As alcohol BIs are delivered by physicians in high income countries [ 3 ], less is known about BIs’ effectiveness when provided by non-professional health workers. In this context, we conducted a randomized controlled trial (RCT) to inform policy makers regarding the potential impact of the national program [ 4 ]. Our main finding was an OR of 0.6 (CI 0.34–1.05) for risk reduction with a p-value of 0.07, from which we concluded that there was no observed effect attributable to the BI, and thus, the program could make better use of resources by not providing one-to-one HT-led interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Then, mixed-effects regressions were used to adjust for demographic variables as xed-effects (age, sex, and educational level) and the health center as random effects. See the main paper for a detailed description of the trial [4].…”
Section: Previous Analysismentioning
confidence: 99%
“…As alcohol BIs are delivered by physicians in high income countries [3], less is known about BIs' effectiveness when provided by non-professional health workers. In this context, we conducted a randomized controlled trial (RCT) to inform policy makers regarding the potential impact of the national program [4]. Our main nding was an OR of 0.6 (CI 0.34-1.05) for risk reduction with a p-value of 0.07, from which we concluded that there was no observed effect attributable to the BI, and thus, the program could make better use of resources by not providing one-to-one HT-led interventions.…”
Section: Introductionmentioning
confidence: 99%